The Affix Changes from Middle English to Modern English Found In The Miller's Tale Written by Geoffrey Chaucer and Its Modern English Version - Egi Putriana; Jufrizal Jufrizal; Fitrawati Fitrawati (Universitas Negeri Padang, 2019)
The history of English language has three periods of time; Old English, Middle English, and Modern English. The linguistic forms in English development are different each period. This research aims to find out one of the changes, that is, the affix changes from Middle English to Modern English form that found in both of The Miller’s Tale Story Middle English and Modern English versions. This research also aims to find out the spelling changes in affixes. This research used descriptive qualitative method. The data, which are the collection of words that have affixes found in The Miller’s Tale, were identified based on the base of the words and its affixes and its were classified based on the type of its functions. Based on data analysis, there are seven affixes in Middle English which have been changed in Modern English form. These changes occur in the deletion of vowel, change of vowel, substitution of the affix, and elimination of the affix. The spelling change also influenced the change in suffixes. Some of the vocabularies change into the new words and some of the words change only in its vowel.